BEST OF THE TECH BLOGS (PR Week, 2009)
13 March I was unaware until today of wikileaks. org, a site that publishes anonymous submissions and leaks of sensitive governmental, corporate, or religious documents, while preserving the anonymity and untraceability of its contributors. The site is a great reference site for journalists, but I can also see how it will be used by PR people wanting to place controlled leaks about their own business or products, and about the actions of competitors.